Caged Gammarus as biomonitors identifying thresholds of toxic metal bioavailability that affect gammarid densities at the French national scale. (1st July 2017) - Ciliberti, Alexandre; Chaumot, Arnaud; Recoura-Massaquant, Rémi; Chandesris, André; François, Adeline; Coquery, Marina; Ferréol, Martial; Geffard, Olivier
Abstract: Bioaccumulated concentrations of toxic elements in biomonitor invertebrate species have already been used to successfully link metal bioavailability and impairments of stream macroinvertebrate communities at the scale of the watershed. However, implementing this empirical comparative approach at a greater spatial scale remains a challenge due to the diversity of biogeographical contexts encompassed by regional and national scales. We showed in previous studies that the use of standard organisms caged permits the use of a common biomonitor over a far greater geographical range, while limiting the influence of confounding factors on levels of bioavailable contamination. In this study, levels of Cd, Hg, Ni and Pb contamination assessed by active biomonitoring with caged Gammarus fossarum were compared to abundances of on-site gammarids on 94 sites in France. Based on this national dataset of in situ bioassays, we first re-determined bioavailable background assessment concentrations (BBACs), i.e. concentrations measured in caged G. fossarum indicating a significant bioavailable contamination, which we had previously defined at a regional scale for these four metallic elements. On-site gammarid abundances were retrieved from monitoring programs implemented by French water agencies for the evaluation of ecological status for the European Water Framework Directive. These abundances were corrected for the influence of stream physico-chemical typology in order to permit a reliable comparison of gammarid densities between sites at the national scale. Clear trends of degradation of gammarid densities with increasing levels of bioaccumulated concentrations were identified for three of the four elements (Cd, Ni and Pb). Threshold concentrations in caged organisms above which the numbers of free-ranging gammarids were abnormally low – namely bioavailable ecological assessment concentrations (BEACs) – were determined. The reliability and validity of the BEACs, their comparison with BBACs and their usefulness in terms of prioritisation of contaminants, sites in freshwater management, are discussed. Graphical abstract: Highlights: Active biomonitoring is relevant for bioavailable contamination assessment. National Bioavailable Background Assessment Concentrations values are proposed. Bioavailable contaminations levels have been calibrated by gammarid abundance. Bioavailable ecological assessment concentrations are proposed for four Water Framework Directive metals.